ANALISIS PENGARUH BAURAN PEMASARAN JASA TERHADAPKEPUTUSAN PEMBELIAN PADA HOTEL ARRAHMAN TEMBILAHAN - Abd. Gaffar '; Jushermi '; Aida Nursanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to measure the effect of marketing mix analysis on purchasing decisions on Arrahman hotel in Tembilahan. The population in this study is that consumers Arrahman hotel in Tembilahan the total sample of 100 respondents using accidental random sampling technique. Analysis of data using multiple linear regression analysis with SPSS version 20.0.Hotel is a company which is managed by their owners by providing food, drink and amenities to rest or sleep to the people who are doing the activity trips and able to pay with a reasonable amount in accordance with the service received in the absence of a special agreement.The results showed that the variables of the marketing mix of services includes product, price, place, promotion, people, process and consumer services simultaneously significant effect on purchasing decisions on Arraman hotel in Tembilahan. Marketing mix including product, price, place, promotion, people, process and customer service is partially significant effect on purchasing decisions on Arrahman hotel in Tembilahan. marketing mix including product, price, place, promotion, people, process and consumer services simultaneously not significant effect on purchase decisions on Arraman hotel in Tembilahan. Marketing mix including product, price, place, promotion, people, process and consumer services partially not significant effect on purchase decisions on Arrahman hotel in Tembilahan.Keywords:Marketing Mix, Purchasing Decisions, and Regression